This is Amiko, do you copy? - Imamura, Natsuko 1980- (Japanese novella series, 2023)
"Other people don't seem to understand Amiko. Whether eating curry rice with her hands at school or peeking through the sliding doors at her mother's calligraphy class, her curious, exuberant nature mostly meets with confusion. When her mother falls into a depression and her brother begins spending all his time with a motorcycle gang, Amiko is left increasingly alone to navigate a world where she doesn't quite fit. Subtle, tender and moving, This is Amiko shows us life through the eyes of a unique, irrepressible, neurodivergent young character." --